Pillar[5]arene-based [1]rotaxanes with salicylaldimine as the stopper: synthesis, characterization and application in the fluorescence turn-on sensing of Zn2+ in water. Issue 64 (21st July 2022) - Ma, Longtao; Tang, Ruowen; Zhou, Youjun; Bei, Jiali; Wang, Yang; Chen, Tingting; Ou, Changjin; Han, Ying; Yan, Chao-Guo; Yao, Yong
Abstract : Unexpected strongly luminescent complexes were constructed via the weakly luminescent [1]rotaxane coordinating with Zn 2+ specifically due to the coordination-induced emission effect. Abstract : Two pillar[5]arene-based [1]rotaxanes with salicylaldimine as the stopper were synthesized and characterized fully, and could be further applied in the fluorescence turn-on sensing of Zn 2+ in water.